Healthy Living Behavior Training as an Effort of Hypertension Problems - Indra Elisabet Lalangpuling; Micahel Valery Tumbol; Allan J. Andaria (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
Based on Riskesdas data in 2018, the prevalence of hypertension based on the results of measurements in the population aged 18 years in Minahasa is 24.11%. The proportion of non-adherence to taking the medication regularly is still high. The proportion of routinely measuring blood pressure on a regular basis is still low. The purpose of this community service is to apply technology in the health sector to improve knowledge and skills, form independent community groups in implementing healthy lifestyle patterns in daily life in controlling blood pressure, being obedient and obedient in using drugs that have been prescribed by doctors. This activity was carried out in Kalasey 2 Village, Minahasa Regency. The method in implementing the activity begins with approaching and socializing the activity plan with the government and coordinating with the Tateli Health Center. The types of activities carried out are counseling on "Healthy Life Behavior Patterns in Daily Controlling Blood Pressure", free health checks for hypertension sufferers, counseling on drug classification, DAGUSIBU and obedient use of antihypertensive drugs, as well as training on the use of POCT/RDT medical devices and tensimeters and management family medicinal plant. The results achieved were that the community group was able to use medical devices for examination and monitoring of health conditions, able to process family medicinal plants, able to implement a healthy diet, able to implement a healthy lifestyle by not consuming alcohol and not smoking, able to comply with prescription antihypertensive drugs. ABSTRAK Berdasarkan data Riskesdas tahun 2018, prevalensi hipertensi berdasarkan hasil pengukuran pada penduduk umur 18 Tahun di Minahasa sebesar 24,11%. Proporsi ketidakpatuhan minum obat secara rutin masih tinggi. Proporsi kerutinan mengukur tekanan darah secara rutin masih rendah. Tujuan dari pengabdian masyarakat ini adalah menerapkan teknologi dalam bidang kesehatan untuk meningkatkan ilmu pengetahuan dan keterampilan, membentuk kelompok masyarakat yang mandiri dalam menerapkan pola perilaku hidup sehat dalam keseharian dalam mengendalikan tekanan darah, patuh dan taat dalam menggunakan obat yang telah diresepkan oleh dokter. Kegiatan ini dilaksanakan di Desa Kalasey 2, Kabupaten Minahasa. Metode dalam pelaksanaan kegiatan diawali dengan melakukan pendekatan dan sosialisasi rencana kegiatan dengan pemerintah dan berkoordinasi dengan Puskesmas Tateli. Jenis kegiatan yang dilakukan adalah penyuluhan tentang “Pola Perilaku Hidup Sehat Dalam Keseharian Dalam Mengendalikan Tekanan Darah”, pemeriksaan kesehatan gratis kepada penderita hipertensi, penyuluhan penggolongan obat, DAGUSIBU dan taat menggunakan obat antihipertensi, serta pelatihan penggunaan alat kesehatan POCT/RDT dan tensimeter serta pengelolaan tanaman obat keluarga. Hasil yang dicapai adalah kelompok masyarakat mampu menggunakan alat kesehatan untuk pemeriksaan dan monitoring kondisi kesehatan, mampu mengolah tanaman obat keluarga, mampu menerapkan diet sehat, mampu menerapkan pola hidup sehat dengan tidak mengkonsumsi alkohol dan tidak merokok, mampu patuh dalam mengkonsumsi obat antihipertensi resep dokter. Kata Kunci: Hipertensi; DAGUSIBU; Tanaman Obat; Pola Hidup Sehat.